Coconut water as a medium additive for the production of docosahexaenoic acid (C22:6 n3) by Schizochytrium mangrovei Sk-02 - Panida Unagul (2018)
The effect of coconut water (CW) on biomass and docosahexaenoic acid (DHA, C22:6 n3) formation by Schizochytrium mangrovei Sk-02 was studied in a yeast extract-diluted sea water medium. Optimal CW-level was ca. 33% (v/v), resulting in a biomass level of 28 g/l with a DHA-content of 20% (w/w) or 6 g DHA/l, almost 50% higher than in non-supplemented cultures at the same initial sugar level. Study on the growth-promoting effects of coconut water suggested that it could be (partially) mimicked by addition of trace elements; the fatty acids present in CW did not appear to be incorporated or effect fatty acid formation by the organism. CW-addition was also effective in media with other nitrogen sources such as casitone, peptone and tryptone. Its inclusion (at 50% v/v) increased biomass levels two-to-three-fold with concomitant increases in the DHA-level. © 2006 Elsevier Ltd. All rights reserved.